Replication timing in Drosophila and its peculiarities in polytene chromosomes - T. D. Kolesnikova; O. V. Antonenko; I. V. Makunin (Вавиловский журнал генетики и селекции)
Drosophila melanogaster is one of the popular model organisms in DNA replication studies. Since the 1960s, DNA replication of polytene chromosomes has been extensively studied by cytological methods. In the recent two decades, the progress in our understanding of DNA replication was associated with new techniques. Use of fluorescent dyes increased the resolution of cytological methods significantly. High-throughput methods allowed analysis of DNA replication on a genome scale, as well as its correlation with chromatin structure and gene activi ty. Precise mapping of the cytological structures of polytene chromosomes to the genome assembly allowed comparison of replication between polytene chromosomes and chromosomes of diploid cells. New features of replication characteristic for D. melanogaster were described for both diploid and polytene chromosomes. Comparison of genomic replication profiles revealed a significant similarity between Drosophila and other well-studi ed eukaryotic species, such as human. Early replication is often confined to intensely transcribed gene-dense regions characterized by multiple replication initiation sites. Features of DNA replication in Drosophila might be explained by a compact genome. The organization of replication in polytene chromosomes has much in common with the organization of replication in chromosomes in diploid cells. The most important feature of replication in polytene chromosomes is its low rate and the dependence of S-phase duration on many factors: external and internal, local and global. The speed of replication forks in D. melanogaster polytene chromosomes is affected by SUUR and Rif1 proteins. It is not known yet how universal the mechanisms associated with these factors are, but their study is very promising.